Framework of Consciousness from Semblance of Activity at Functionally LINKed Postsynaptic Membranes - Vadakkan, Kunjumon I. (Frontiers in Psychology, 2010)
Consciousness is seen as a difficult “binding” problem. Binding, a process where different sensations evoked by an item are associated in the nervous system, can be viewed as a process similar to associative learning. Several reports that consciousness is associated with some form of memory imply that different forms of memories have a common feature contributing to consciousness. Based on a proposed synaptic mechanism capable of explaining different forms of memory, we developed a framework for consciousness. It is based on the formation of semblance of sensory stimulus from 1)synaptic semblances when excitatory postsynaptic potentials arrive at functionally LINKed postsynaptic membranes, and 2) network semblances when these potentials summate to elicit action potential initiating activity in a network of neurons. It is then possible to derive a framework for consciousness as a multi-dimensional semblance. According to this framework, a continuum of semblances formed from background sensory stimuli and oscillating neuronal activities serve to maintain consciousness. Feasibility of this framework to explain various physiological and pathological states of consciousness, its subjective nature and qualia is examined.